Prevalence and risk factors of general and abdominal obesity and hypertension in rural and urban residents in Bangladesh: a cross-sectional study - Nurshad Ali; Nayan Chandra Mohanto; Shaikh Mirja Nurunnabi; Tangigul Haque; Farjana Islam (BMC, 2022)
Abstract Background Obesity and hypertension are global health concerns. Both are linked with increased risks of all-cause and cardiovascular mortality. Several early studies reported the prevalence of obesity and hypertension in Bangladeshi adults, but the associated factors in this country population are not clear yet. We aimed to estimate the prevalence and related risk factors of general and abdominal obesity and hypertension in rural and urban adults in Bangladesh. Methods In this cross-sectional study, data (n = 1410) was collected on rural (n = 626) and urban (n = 784) adults from eight divisional regions of Bangladesh. Both anthropometric and socio-demographic measurements were recorded in a standardized questionnaire form. General and abdominal obesity were defined based on WHO proposed cut-off values and hypertension was defined by SBP ≥ 140 mmHg and/or, DBP ≥ 90 mmHg and/or, intake of anti-hypertensive drugs at the time of data collection. Multivariable logistic regression analyses were performed to assess the relationship of general and abdominal obesity and hypertension with various factors. Results The overall prevalence of general obesity, abdominal obesity and hypertension was 18.2, 41.9 and 30.9%, respectively. The women had a higher prevalence of general obesity (25.2%), abdominal obesity (56.1%) and hypertension (32.3%) compared to the men (12.2, 29.0, and 29.7%, respectively). The prevalence of both general and abdominal obesity was higher in urban participants (21.7 and 46.6%, respectively) than in the rural participants (13.8 and 35.1%, respectively), whereas, the rural participants had a higher prevalence of hypertension (35.1%) compared to the urban participants (27.5%). In geographical region comparison, the prevalence of general and abdominal obesity and hypertension were higher in participants enrolled from Dhaka (30.8%), Khulna (63.6%) and Mymensingh (43.5%) regions, respectively compared to other regions. In regression analysis, increased age, place of residence and less physical activity were positively associated with the increased risk of both types of obesity and hypertension. The analysis also showed a significant positive association between high BMI and an increased risk of hypertension. Conclusion This study shows a high prevalence of obesity and hypertension in rural and urban adults. Increased age, inadequate physical activity and place of residence were significant determinants of general and abdominal obesity and hypertension. A comprehensive intervention program focusing on modifiable risk factors such as lifestyles and food habits is needed to increase awareness and prevent the burden of obesity and hypertension in the Bangladeshi population.